No Consistent Evidence of Decreased Exposure to Varicella-Zoster Virus Among Older Adults in Countries with Universal Varicella Vaccination. (5th October 2021) - Carryn, Stephane; Cheuvart, Brigitte; Povey, Michael; Dagnew, Alemnew F; Harpaz, Rafael; van der Most, Robbert; Casabona, Giacomo
Abstract: Background: Universal varicella vaccination might reduce opportunities for varicella-zoster virus (VZV) exposure and protective immunological boosting, thus increasing herpes zoster incidence in latently infected adults. We assessed humoral and cell-mediated immunity (CMI), as markers of VZV exposure, in adults aged ≥50 years. Methods: We repurposed data from placebo recipients in a large multinational clinical trial (ZOE-50). Countries were clustered based on their varicella vaccination program characteristics, as having high, moderate, or low VZV circulation. Anti-VZV antibody geometric mean concentrations, median frequencies of VZV-specific CD4 T cells, and percentages of individuals with increases in VZV-specific CD4 T-cell frequencies were compared across countries and clusters. Sensitivity analyses using a variable number of time points and different thresholds were performed for CMI data. Results: VZV-specific humoral immunity from 17 countries (12 high, 2 moderate, 3 low circulation) varied significantly between countries ( P  < .0001) but not by VZV circulation. No significant differences were identified in VZV-specific CMI between participants from 2 high versus 1 low circulation country. In 3/5 sensitivity analyses, increases in CMI were more frequent in high VZV circulation countries (.03 ≤  P  < .05). Conclusions: We found no consistent evidence of reduced VZV exposure among older adults in countries with universal varicella vaccination. Clinical Trials Registration: NCT01165177. Abstract : By repurposing humoral and cell-mediated immunogenicity data from a large multinational trial enrolling adults aged ≥50 years, we found no consistent evidence of differences in varicella-zoster virus exposure between countries with widely circulating varicella versus countries with universal vaccination.